The lexeme tęcza [rainbow] in contemporary Polish presented against cultural background and other Slavic languages - Święcicka, Małgorzata; Peplińska, Monika (Papers in Linguistics, 2025)
The aim of the article is to provide linguistic and cultural reflection on the lexeme tęcza. Considering its cultural background and correspondents in other Slavic languages, the proposed analysis covers the semantics of the word in Polish and is an attempt to situate the term in the thematic fields of Polish. The presented findings and their analysis confirm that the lexeme in question is a universal concept, with rich symbolism and generally positive cultural connotations. The authors point to the presence of the word in many European languages, including Slavic ones, to denote various atmospheric phenomena accompanying the rainbow. The ambiguity of the word in Polish as well as its basic, literary, figurative and specialized meanings justify lexicological thematic qualification to fields such as: man and nature, physical categories, man and technology, everyday human life.